Peter Norton's introduction to computers - Norton, Peter; Norton, Peter (New York : Glencoe McGraw-Hill, 2001)
This completely revised edition of Introduction to Computers offers a comprehensive grounding in computer concepts, reflecting some of the latest advances in technology, to prepare students for the next level of computer productivity. It includes three entirely new chapters on the Internet, computer graphics, and multimedia.
Unit 1. The Amazing Computer -- Sect. 1A. Introduction to Computer Systems -- Sect. 1B. Introduction to the Internet -- Unit 2. Interacting With Your Computer -- Sect. 2A. Standard Input Devices -- Sect. 2B. Alternative Input Devices -- Unit 3. Output Devices -- Sect. 3A. Monitors and Sound Systems -- Sect. 3B. Devices That Output Hard Copy -- Unit 4. Processing Data -- Sect. 4A. Transforming Data Into Information -- Sect. 4B. CPUs Used in Personal Computers -- Unit 5. Storing Information in a Computer -- Sect. 5A. Types of Storage Devices -- Sect. 5B. Measuring and Improving Drive Performance -- Unit 6. The Operating System and User Interface -- Sect. 6A. Operating System Basics -- Sect. 6B. PC Operating Systems -- Unit 7. Networks and Data Communications -- Sect. 7A. Networking Basics -- Sect. 7B. Networking the Home, the Office, and the Globe -- Unit 8. The Internet and Online Resources -- Sect. 8A. Internet Basics -- Sect. 8B. Getting Online, Working Online -- Unit 9. Application Software: Word Processors and Spreadsheets -- Sect. 9A. Word Processing and Desktop Publishing Software -- Sect. 9B. Spreadsheet Software -- Unit 10. Application Software: Presentation Programs and Databases -- Sect. 10A. Presentation Programs -- Sect. 10B. Database Management Systems -- Unit 11. Graphics and Multimedia -- Sect. 11A. Graphics and Graphics Software -- Sect. 11B. Understanding Multimedia -- Unit 12. Development of Information Systems -- Sect. 12A. The Basics of Information Systems -- Sect. 12B. Building Information Systems -- Unit 13. Software Programming and Development -- Sect. 13A. Creating Computer Programs -- Sect. 13B. Programming Languages and the Programming Process -- Unit 14. Living With Computers -- Sect. 14A. Computers and the Individual -- Sect. 14B. Computing Issues That Affect Us All -- App. A. The History of Microcomputers -- App. B. Self Check Answers.
Includes index.
Keywords: COMPUTERS